Intersecting Aesthetics of Suffering: Emotional Expression and Clinical Realism in “The Stories of Shanti” and “The Steel Windpipe” - Joshi, Bhup Raj (Innovative Research Journal, 2025)
This article builds on the complexity of suffering as manifest in the two texts, “The Stories of Shanti: Culture and Karma” and Mikhail Bulgakov’s “The Steel Windpipe” that foreground the interaction of emotional expression, culture, clinical realities, and ethical concerns. It explores the conflict of traditional healing paradigms in relation to contemporary medical practice. A comparative textual analysis approach to illustrate how suffering is constructed, defined, and experienced across different cultural worlds and how, by extension, medical practitioners navigate ethical duties amid cultural safety concerns regarding biomedical requirements has been used. Bringing together the religious readings of suffering, personal testimony, and elements of medical realism, it argues that suffering is not only an individual pathology but is relational, culturally mediated, and spiritually interpretive. The representations of Shanti and Lidka illustrate how meaning-making, emotional resilience, generosity, familial involvement, and medical ethics (both patient-centered and in relation to their caregivers), can shape the lived experience of illness. The concluding remark of this paper is that suffering is not just a physical state but also rather an integrated state of mind, body, and spirit, influenced by different cultural perspectives.